The intramembrane protease SPPL2a promotes B cell development and controls endosomal traffic by cleavage of the invariant chain - Schneppenheim, Janna (The Rockefeller University Press, 2013)
Regulated intramembrane proteolysis is a central cellular process involved in signal transduction and membrane protein turnover. The presenilin homologue signal-peptide-peptidase-like 2a (SPPL2a) has been implicated in the cleavage of type 2 transmembrane proteins. We show that the invariant chain (li, CD74) of the major histocompatability class II complex (MHCII) undergoes intramembrane proteolysis mediated by SPPL2a. B lymphocytes of SPPL2a(−/−) mice accumulate an N-terminal fragment (NTF) of CD74, which severely impairs membrane traffic within the endocytic system and leads to an altered response to B cell receptor stimulation, reduced BAFF-R surface expression, and accumulation of MHCII in transitional developmental stage T1 B cells. This results in significant loss of B cell subsets beyond the T1 stage and disrupted humoral immune responses, which can be recovered by additional ablation of CD74. Hence, we provide evidence that regulation of CD74-NTF levels by SPPL2a is indispensable for B cell development and function by maintaining trafficking and integrity of MHCII-containing endosomes, highlighting SPPL2a as a promising pharmacological target for depleting and/or modulating B cells.